Sugar cane bagasse ash as a pozzolanic material (2017)
This study aimed to verify the SCBA's potential use as a partial replacement of Portland cement. Therefore, the experiment was divided in two stages; in the first, mineralogical and chemical analyses were performed with two samples of ash, in-natura and calcined at a temperature of 600°C for 6h. After these analyzes, it was observed that the calcined ash presented a greater tendency of material in the amorphous state, which possibly made the material the most reactive. For this reason, only the calcined ash was ground for 1 and 2h. These samples were further studied in order to check the pozzolanic activity index and the compressive strength, evaluating the replacement of 10, 20 and 30% Portland cement by ground SCBA. The results showed an increase in the pozzolanic activity index only in samples of calcined and ground SCBA, showing that calcined ash must undergo a grinding process to present pozzolanic activity.